Pembagian Warisan Pada Perkawinan Poligami - Jauhari, Jauhari; Candra, Andi; Afriani, Kinaria (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Islamic inheritance is the law that regulates the transfer of inheritance rights (tirkah) of heirs, determining who has the right to become heirs and how much each person will share. Polygamy is defined as a marriage in which a man has more than one wife. What is problematic in polygamous marriages is the distribution of inheritance. Where when the husband dies and leaves property, the wife's rights also include the wife's rights which must be distributed fairly. Islamic inheritance law basically does not recognize or recognize the concept of joint property itself, this is because there are no provisions in either the Qur'an or hadith. Meanwhile, positive law has not implemented the provisions contained in Islamic law itself.